(untitled) (Asian Education Studies, 2020)
This paper expounds a process of music teaching and learning. It is a project and it contains project outline, practicum log and evaluation. The purpose of the project is to strengthen the pupil’s reading skills in pitch and rhythmic accuracy. The duration of the project is four weeks. This article reflects a specific process and influence from student by studying piano. Also, it provides some practical suggestion and reflection to teacher.